Making an Accurate Diagnosis of Chronic Hypersensitivity Pneumonitis - Kerri A Johannson; Christopher J Ryerson (Canadian Respiratory Journal)
Chronic hypersensitivity pneumonitis (HP) arises from repeated exposure to causative antigens. Although HP can be challenging to diagnose, it is important to differentiate from idiopathic pulmonary fibrosis and idiopathic non-specific interstitial pneumonia. HP has a unique management approach and portends a unique prognosis. The present article summarizes the recent published literature on chronic HP and highlights the features that may be helpful in distinguishing it from other chronic interstitial lung diseases.